Endocrinology of Physical Activity and Sport Second Edition - Constantini, Naama; Hackney, Anthony C.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
Understanding the influence and interaction between physical activity and the endocrine system are of paramount importance in dealing with a multitude of health problems. In Endocrinology of Physical Activity and Sport, renowned physicians and researchers provide a comprehensive and expanded update on the scientific, clinical and practical components of endocrinology as related to sport and exercise. The authors thoroughly review what is known about how such activity affects the endocrine system and how in turn these hormonal responses affect many other organs and systems of the body. In addition, aspects of endocrinology in non-glandular tissue which have endocrine actions are addressed; for example, adipocytes and the release of leptin and related adipocytokines. Further, a wide range of clinically related topics such as athletic amenorrhea, osteopenia, sarcopenia, and hypogonadism are included. This new edition critically integrates what is known about the complex interaction of the endocrine system in the sports context and will again prove immensely valuable to all physicians and clinical investigators treating those active in sports today.
Methodological Considerations in Exercise Endocrinology -- Exercise and Endogenous Opiates -- The Effect of Exercise on the Hypothalamo-Pituitary-Adrenal Axis -- Impact of Chronic Training on Pituitary Hormone Secretion in the Human.-Exercise and the GH-IGF-I axis -- Exercise and Thyroid Function -- The Male Reproductive System, Exercise and Training: Endocrine Adaptations -- Exercise and the Hypothalamus. Ovulatory Adaptations -- Adrenergic Regulation of Energy Metabolism.- Energy Balance and Weight Control (male and female): Considerations.-Exercise Training in the Normal Female: Effects of Low Energy -- Availability on Reproductive Function.-Ghrelin Responses to Acute Exercise and Training -- Hormonal Regulation of Fluid and Electrolyte Homeostasis During Exercise -- Hormonal Regulations of the Effects of Exercise on Bone. Positive and Negative Effects -- Interrelations Between Acute and Chronic Exercise Stress and the Immune and Endocrine Systems -- Effect of Female Reproductive Hormones on Sports Performance -- Exercise and Pregnancy: Hormonal Considerations -- Vitamin D and Exercise Performance -- The effects of altitude on the hormonal response to physical exercise -- An Introduction to Circadian Endocrine Physiology - Implications for Exercise and Sports Performance -- Physical Activity and Mood. The Endocrine Connection -- Endocrine Responses to Acute and Chronic Exercise in the Developing Child.- Exercise in Older Adults: The Effect of Age on Exercise Endocrinology -- Oncology Patients and Aerobic Exercise: Immune System, Endocrine System, and Soluble Factor Responses -- Diabetes and Exercise -- Extreme Sports and Type 1 Diabetes Mellitus: An oxymoron or a growing reality?- The Endocrine System in Overtraining -- Hormones as Performance Enhancing Agents.
Keywords: Endocrinology .; Internal medicine; Endocrinology; Internal Medicine